Recreational activity motivation and perceived health outcomes in recreation from men’s perspective - Mustafa İnan Özant; Tebessüm Ayyildiz Durhan; Mehmet Demirel; Erdal Zorba (Journal of Men's Health)
Background: This study aims to determine the motivations for recreational activities and perceived health outcomes in recreation in men. At the same time, the findings obtained in this study, which set out to determine the relationship and effect between recreational activity motivation and perceived health outcomes in recreation, tried to reveal the difference created by the variables on the measurement tools. Methods: Data were collected from university students in Ankara between April and July 2024. In this context, 684 individuals participating in recreational activities were included. The data were obtained using the Recreational Activity Motivation Scale and Perceived Health Outcomes in Recreation Scale as well as the personal information form. Results: The findings showed that various variables differentiated the measurement tools, there were strong positive relationships between the measurement tools, and the measurement tools had an effect to explain each other by 50%. Conclusions: As a result, the assumption that male participants’ motivation towards recreational activities was high, that the health outcomes they obtained through participation in recreational activities were high in parallel with this, that various variables differentiated this situation, and that health outcomes could be increased with high motivation was confirmed.